Meter and modernity in English verse, 1350-1650 - Weiskott, Eric (University of Pennsylvania Press, 2021)
Eric Weiskott examines the uses and misuses of three metrical forms as markers of literary periodization: alliterative meter, tetrameter, and pentameter. Rejecting the traditional division between medieval and modern, Weiskott's analysis of metrical history renegotiates the trajectories of English literary history between 1350 and 1650.